Critical review on innovation in poultry feed - Ong, Jin Ling; Arriffin, Ahmad Shabudin (2015)
This research aims to determine the innovation in poultry feed practices among poultry producers. Poultry is a domestic that includes chicken, ducks and so on.They produced eggs and meat as food for consumers.The accepted sizes of birds are 2kg that growth within six weeks.By interviewing to the farm owners, revealed raw materials of feed are imported from the foreign countries. Vitamin and drugs for broilers also imported from foreign countries.The production of feed will increase when the demand is increased in the market. The profit of the product is depends on the price of the raw material of feed that imported.To make sure feedings is enough for broilers and not wasted from the feeding system, innovation in technology also needed.Technology will helped in distributing the feeds to broilers equally with automatic system.By using innovation of technology, there are some benefits for poultry producers such as save labour cost. But there is no innovation in feed in Malaysia poultry farms. Although innovation of feed have its benefits, but for the producers are not really interested and still practiced the same way.